2001
DOI: 10.1159/000049328
|View full text |Cite
|
Sign up to set email alerts
|

The Delusions of Capgras and Intermetamorphosis in a Patient with Right-Hemisphere White-Matter Pathology

Abstract: Previous neuropsychological studies have demonstrated an association between person misidentification and right-hemisphere dysfunction. In the study reported here, we explore the contribution of facial and visual recognition impairments in a patient with right-hemisphere subcortical white-matter pathology in the frontal and parietal lobes and a diagnosis of vascular cognitive impairment. The patient displayed false recognition of unfamiliar faces and deficient retrieval of key biographic detail for famous face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
2
31
0
2
Order By: Relevance
“…Previous reports have been largely restricted to grey matter, and as far as we know, there was only one previous report of WMH lesions affecting the brainstem in DMS 6 . The presence of deep WMH suggests that DMS could result from a disruption of connections involving frontal lobe to other cortical and subcortical areas.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Previous reports have been largely restricted to grey matter, and as far as we know, there was only one previous report of WMH lesions affecting the brainstem in DMS 6 . The presence of deep WMH suggests that DMS could result from a disruption of connections involving frontal lobe to other cortical and subcortical areas.…”
Section: Discussionmentioning
confidence: 93%
“…Previous authors have suggested that impairment in facial recognition plays a role in the pathogenesis of DMS 6 . Some studies have demonstrated impairment in judging facial emotions in patients with the diagnosis of schizophrenia associated to a global impairment in social skills which results from a right hemisphere dysfunction.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations